2001
DOI: 10.1038/sj.bjp.0704068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemically modified tetracyclines (CMTs) in sensitive, multidrug resistant and apoptosis resistant leukaemia cell lines

Abstract: 1 Recently discovered chemically modi®ed tetracyclines (CMTs) have shown in vitro and in vivo anti-proliferative and anti-tumour activities. Here, we evaluated in vitro the anti-proliferative and apoptotic activity of six di erent dedimethylamino chemically modi®ed tetracyclines (CMT-1, CMT-3, CMT-5, CMT-6, CMT-7 and CMT-8) in sensitive and multidrug resistant myeloid leukaemia cells (HL60 and HL60R) in vitro. 2 Three of these compounds (CMT-5, CMT-6, CMT-7) showed low cytotoxic activity both in sensitive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The chemically modified tetracyclines (CMTs), devoid of antibacterial activity, also attenuate some manifestations of the inflammatory response (Patel et al, 1999;D'Agostino et al, 2001;Sandler et al, 2005). Furthermore, some CMTs induce apoptosis in multidrug-and apoptosis-resistant leukaemia cell lines, and these effects underlie their potential antitumour activity (Tolomeo et al, 2001). Indeed, the efficacy and safety of incyclinide, also known as CMT-3, have been evaluated in clinical trials for the treatment of acne and some types of cancer (www.clinicaltrials.gov).…”
Section: Introductionmentioning
confidence: 99%
“…The chemically modified tetracyclines (CMTs), devoid of antibacterial activity, also attenuate some manifestations of the inflammatory response (Patel et al, 1999;D'Agostino et al, 2001;Sandler et al, 2005). Furthermore, some CMTs induce apoptosis in multidrug-and apoptosis-resistant leukaemia cell lines, and these effects underlie their potential antitumour activity (Tolomeo et al, 2001). Indeed, the efficacy and safety of incyclinide, also known as CMT-3, have been evaluated in clinical trials for the treatment of acne and some types of cancer (www.clinicaltrials.gov).…”
Section: Introductionmentioning
confidence: 99%
“…The apoptotic activity of CMTs has been proposed to be related to the absence of the 4-dimethylamino group at the carbon atom [44]. The induction of apoptosis by CMTs has been reported in several different cell types and disease models [43][44][45][46][47]. It has been suggested that CMTs induce mitochondria-mediated apoptosis through both caspasedependent and -independent pathways.…”
Section: Tetracyclines Modulate the Apoptotic Cascadementioning
confidence: 98%
“…They induce typical morphological changes, increase the activity of several caspases, increase the level of cytosolic cytochrome c and change the balance of Bax/Bcl-2 protein expression [43][44][45][46][47][48]. Tetracyclines have been shown to induce apoptosis of many immune system cells such as mast cells [47], T lymphocytes [49] and macrophages [43].…”
Section: Tetracyclines Modulate the Apoptotic Cascadementioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we report the encapsulation of tetracycline (TC), an antibiotic, within the apoferritin cavity owing to the recent implications of the cytostatic and cytotoxic capacities of TC on tumor cells of many different origins, both in vitro and in animal models . It would also be worthwhile if the apoferritin–TC complex could be tracked within the biological system.…”
Section: Introductionmentioning
confidence: 99%